Mathematical analysis of the 09 March 2012 intense storm - Koklu, Kevser (ELSEVIER SCI LTD, 2020)
The in-depth investigation of the parameters of the solar wind, the zonal geomagnetic indices and the interplanetary magnetic field (IMF) is the key to furthering space weather researches. The investigations got meaning through modeling various interplanetary parameters and geomagnetic indices. These models, built on the basis of the correlations between solar wind parameters and zonal geomagnetic indices, and that must strictly obey physical principles, will not only reveal the properties of geomagnetic activity but also allow estimates of their formations. This study focuses on the 2012 March 09 phenomenon, the first intense geomagnetic storm of the 24th solar cycle. The deeper understanding of the storm depends on a correct interpretation and visualization of the relationship between solar wind plasma parameters (solar wind dynamic pressure (P), flow speed (v), electric field (E), magnetic field (B-z), proton density (N), temperature (T)) and zonal geomagnetic indices (AE, ap, Kp, Dst). The study investigates, visualizes and interprets the solar wind plasma parameters and zonal geomagnetic indices themselves. The storm variables set included of observations of ten variables from NASA are described. By this investigation a covariance matrix indicates the strength of bivariate relationships, a dendrogram indicates hierarchical clustering into groups, and factor analysis indicates three distinct eigenvectors. In addition, linear and nonlinear models about the problem are introduced to readers. The author discuses mathematically what happened in the storm on 2012 March 09 at the beginning of the 24th solar cycle. The aim of this work is to help the reader understand the storm by providing the models that the representatives of parameters and indices coexist. (C) 2020 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: Mathematical modelling; Solar wind parameters; Zonal geomagnetic indices; SOLAR-WIND PARAMETERS; ENERGY; Engineering; Astronomy & Astrophysics; Geology; Meteorology & Atmospheric Sciences